West's Business Law - Kenneth W. Clarkson... (South-Western College/West, 2003)
This interactive CD-ROM Edition is based on the best selling print version of West's Business Law, 9th Edition. This CD-ROM can be used as a stand alone item or in conjunction with the text. This CD-ROM appeals to those looking to experience business law in a whole new way and medium. Along with inclusion of the entire WestÂ's Business Law text, this CD-ROM includes video segments, full case presentations, a built-in study guide, quizzes, self-tests and more.